Secrecy performance of mixed single-input multiple-output-FSO/single-input multiple-output-RF networks with energy harvesting - He, Wanxin; Zhang, Jiliang (Applied optics. Optical technology and biomedical optics, 2021)
In this paper, we study the secrecy performance of an energy-harvested relaying assisted free space optical-radio frequency (FSO-RF) network. In particular, a single-beam source sends an optical signal to a multi-aperture relay over an FSO channel, and then the relay converts it into an RF signal and adopts a decode-and-forward protocol to forward it to a multi-antenna destination under the wiretapping of a multi-antenna eavesdropper. We assume that the relay is power constrained, and it requires to harvest energy from a power beacon to assist the information transmission. It is also assumed that the FSO link and all RF links are subject to gamma-gamma fading with atmospheric turbulence and Rayleigh fading, respectively. Analytical expressions for secrecy outage probability (SOP) and the probability of strictly positive secrecy capacity are derived. In addition, the asymptotic expression for SOP is obtained to present insight into secrecy performance at high signal-to-noise ratio regimes. Finally, Monte Carlo simulations verify the correctness of the theoretical derivations.